From the battlefield to main street: Tourniquet acceptance, use, and translation from the military to civilian settings. Issue 1 (July 2019) - Goodwin, Tress; Moore, Krista N.; Pasley, Jason David; Troncoso, Ruben; Levy, Matthew J.; Goolsby, Craig
Abstract : ABSTRACT: Throughout history, battlefield medicine has led to advancements in civilian trauma care. In the most recent conflicts of Operation Enduring Freedom in Afghanistan/Operation Iraqi Freedom, one of the most important advances is increasing use of point-of-injury hemorrhage control with tourniquets. Tourniquets are gradually gaining acceptance in the civilian medical world—in both the prehospital setting and trauma centers. An analysis of Emergency Medical Services (EMS) data shows an increase of prehospital tourniquet utilization from 0 to nearly 4, 000 between 2008 and 2016. Additionally, bystander educational campaigns such as the Stop the Bleed program is expanding, now with over 125, 000 trained on tourniquet placement. Because the medical community and the population at large has broader acceptance and training on the use of tourniquets, there is greater potential for saving lives from preventable hemorrhagic deaths.